Isolation and biochemical and functional characterization of perforin 1 from cytolytic T-cell granules. - Podack, E R (1985)
The Ca2+-dependent cytolytic activity of isolated T-lymphocyte granules was purified to apparent homogeneity by high-salt extraction, gel filtration, and ion-exchange chromatography. The lytic activity resided in a 72- to 75-kDa protein of cytolytic granules. Incubation of the isolated protein with erythrocytes in the presence of Ca2+ ions resulted in hemolysis and the formation of membrane lesions of 160 A in diameter, corresponding in size and morphology to membrane lesions formed on target cells by cloned, intact natural killer (NK) and cytolytic T lymphocytes. Hence, the 75-kDa granule protein is identified as monomeric perforin 1 (P1), postulated previously from the analysis of membrane lesions formed during NK and T-cell-mediated cytolysis. P1-mediated hemolysis is Ca2+-dependent and is inhibited by Zn2+ ions. Lysis is accompanied by the polymerization of P1 to membrane-associated tubular complexes (poly-P1) that form large transmembrane pores. P1 causes a rapid membrane depolarization of J774 cells in the presence of Ca2+. Purified P1 also induces transmembrane monovalent and divalent ion flow across lipid vesicles only in the presence of Ca2+. Whole-cell patch-clamp recordings of S49 lymphoma cells show a P1-dependent inward membrane current flow in the presence but not in the absence of Ca2+. The current increase can be dissected as a summation of discrete current events, indicative of formation of functional channels by polymerization of P1.